STING-Associated Vasculopathy with Onset in Infancy: A Review Focusing on Pathophysiology and Treatment Options - Konstantinos Drougkas; Roubini Smerla; Charalampos Skarlis; Clio P. Mavragani (MDPI AG, 2023)
STING-associated vasculopathy with onset in infancy (SAVI) is a rare type Ι interferonopathy caused by gain of function mutations in an encoding stimulator of interferon genes (STING) protein 1. SAVI is characterized by neonatal or infantile-onset systemic inflammation, mainly affecting peripheral cutaneous blood vessels, skin, and lungs. The main disease manifestations include recurrent febrile episodes, cough, dyspnea, and failure to thrive, in association with progressive interstitial lung disease, polyarthritis, and cold-induced red violet plaques or papules on fingers, knees, toes, heels, nasal tip, and ears that can lead to distal ulcerations, skin necrosis, tissue loss, and autoamputation. For the management of SAVI, JAK inhibitors can be a valuable therapeutic intervention that hampers disease progression, while conventional immunosuppressive treatments have shown minimal efficacy. This review aims to describe the underlying pathophysiologic mechanisms of SAVI, highlighting the main clinical manifestations and discussing the current treatment approaches.